Survey about impact voltage instability and transient stability for a power system with an integrated solar combined cycle plant in Iraq by using ETAP - Abass, Ahmed Zkear; Pavlyuchenko, D.A; Saadallah Hussain, Zozan (Universitas Muhammadiyah Yogyakarta, 2021)
The Analyses for power systems are more necessary for the designing, operating phase execution control and to make sure safe network operations by sufficient protection project settings. In this article, we have prepared a sufficient scientific survey about the electrical model of a 340 MW integrated solar combined cycle system (ISCCS) located in the Iraqi southern, is developed and simulation by a program called Electrical Transient Analyzer Program (ETAP) and carry out throw this program the load flow, voltage stability and short circuit analyses for this power plant with part of the national grid in Al-Basra city in an industrial region. The effect of voltage instability for the grid on system buses (load buses) of the power system is estimated. By using load flow analysis as a case study by using the Newton-Raphson algorithm, when the load buses operating at down voltage because of instability voltage of the power grid are specified and their voltages are should to improved according to given voltage limitations that are depended on buses criticality with regard to loads. The appliance on-load tap changers of the transformer and reactive power compensation are used to improve steady-state voltage stability for any instability system. The method of the optimal position for capacitor banks placement is meaning the number of capacitor banks is proposed to adding to the weak buses by using the optimal capacitor placement module of ETAP. Energy is actually required for the expansion of our country. To sustain the generation of electric power at an adequate level power system supplies power to different types of loads that are located far away from the generating plants using transmission lines.